Contemporary labor economics - McConnell, Campbell R.; Brue, Stanley L. , 1945-; Macpherson, David A. , 1960- (The McGraw-Hill series economics, 2013)
Presents labor economics as an applied field of micro and macro theory, no longer an area tangential to the core of analytical economics, but rather a critical component of that core. This edition delivers discussions of public policy issues and coverage of the economic crisis, while still integrating traditional topics such as labor law